2015
DOI: 10.5539/jfr.v5n1p26
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Algerian Honey from Tiaret Region and Immunoassay Study of Its Immunomodulatory Effect in BALB/c Mice

Abstract: Honey is a food that possesses several antiseptic, antibacterial, anti-inflammatory and immunomodulatory properties. In this study, the immunomodulatory effect of honey was evaluated by Enzyme Linked Immunosorbent Assay (ELISA) using ovalbumin as an allergen model. To compare the honey quality, we conducted a range of physicochemical analyses on four different samples from the Tiaret region (Algeria) using the immunosuppressive or immunomodulatory effect in Balb/c mice. Our results show that the injection of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…From Table 2 , the analysis of honey samples showed that all of the tested Algerian honey samples were acidic in nature, with pH values that varied between 3.19 and 4.54. It was reported previously that the pH values of Algerian honey ranged from 3.70 to 4.00 [ 31 ] and 3.96 to 4.34 [ 32 ]. The acidity of any honey is directly related to the floral sources that created it.…”
Section: Discussionmentioning
confidence: 99%
“…From Table 2 , the analysis of honey samples showed that all of the tested Algerian honey samples were acidic in nature, with pH values that varied between 3.19 and 4.54. It was reported previously that the pH values of Algerian honey ranged from 3.70 to 4.00 [ 31 ] and 3.96 to 4.34 [ 32 ]. The acidity of any honey is directly related to the floral sources that created it.…”
Section: Discussionmentioning
confidence: 99%